One Stage Transanal Full Thickness Pull-Through for Hirschsprung’s Disease: A Report on Six Years Operation Experience with Iraqi Infants and Children - Sarmad Jaafar Mohammed Alrubaye,; Ban Waheed Hussein Bdair,; Satar Jabbar Rahi Algraittee,; Dr. Haider Jebur Kehiosh,; Dr.Nazar Jebbar Metib, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: In the past two decades, the traditional surgical techniques for Hirschsprung's disease (HD) have evolved from numerous stages with stoma formation to a more modern one-step surgery with low invasiveness as well as low patient morbidity. The transanal full-thickness rectal resection procedures and case studies are presented in this study. All surgeries were performed at the Al-Kafeel Super Speciality Hospital in Kerbala, Iraq. Methods:This retrospective study was done in a single unit, from March 2016 to December 2022. Prior to surgery, contrast edema was performed on 100 patients who met the inclusion criteria, such as uncomplicated and short-segment. All patients who met the inclusion criteria were included in this study's clinical, surgical, and follow-up phases; individuals with colostomies, ileostomies, or any other abdominal interference were not included. Results:The average age of the 100 patients at the time of surgery was 4 months (120 days). At the end of the neonatal phase (first month), three patients received surgery. Ninety patients had their transition zone identified using a contrast enema study, surgical dissection, and rectosigmoid excision. Two patients needed red blood cell transfusions, and the average amount of blood loss was 25 mL. After 24 hours, the average full feeding time occurred. The average hospital-stay before and after surgery, was 3 days. NSAIDS were used to provide analgesia to all patients. Early postoperative complications included stricture (4%), enterocolitis (5%), perianal excoriation (20%), and spasm of the anal sphincter muscle (10%). The patients were monitored for roughly 36 months; 90% of them had age-appropriate normal bowel function, 6% had minor issues, and 4% had serious issues. For anastomotic leak in two patients, severe stricture in two patients who did not respond to anal dilatation in two patients and residual aganglionosis in one patient, a second operation was necessary. Conclusion:One stage Transanal full-thickness pull-through can be a safe treatment if executed correctly and it promises a successful outcome, especially for patients with short ganglionic segments suffering from HD. Early feeding, early release, no transabdominal investigation, decreased morbidity, and happiness for the family and the baby in the future are all made possible by this procedure.